1991
DOI: 10.1080/00332747.1991.11024563
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement and Heightened Existential Awareness

Abstract: "Ask not for whom the bells toll; they toll for thee." John Donne's admonition, though written 350 years ago, endures with astonishing freshness; it speaks to something self-evident, to a truth that is well known to many who have experienced bereavement--that the death of a significant other has the potential to hurl the survivor into a confrontation with his/her own death. A confrontation with death--should we seek it? There is evidence in the clinical literature that in terminally ill patients such a confron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(103 citation statements)
references
References 8 publications
2
97
0
4
Order By: Relevance
“…Positive changes such as increased strength, empathy and connectedness with others, increased compassion (Calhoun & Tedeschi, 2001), "enhanced personal resources" (Schaefer & Moos, 2001), enhanced "existential awareness" (Yalom, Lieberman, & Morton, 1991) and "spiritual change" (Balk, 1999) have been reported. In fact, it has been observed that bereavement research is moving towards a growth-oriented paradigm (Rothaupt & Belker, 2007).…”
Section: Post-traumatic Growthmentioning
confidence: 99%
“…Positive changes such as increased strength, empathy and connectedness with others, increased compassion (Calhoun & Tedeschi, 2001), "enhanced personal resources" (Schaefer & Moos, 2001), enhanced "existential awareness" (Yalom, Lieberman, & Morton, 1991) and "spiritual change" (Balk, 1999) have been reported. In fact, it has been observed that bereavement research is moving towards a growth-oriented paradigm (Rothaupt & Belker, 2007).…”
Section: Post-traumatic Growthmentioning
confidence: 99%
“…This leads to a growing body of research, which reveals that many trauma survivors also experience positive psychological changes after this experience. Different terms have been used to describe this phenomenon: stress-related growth (Park, Cohen & Murch, 1996;Park & Hegelson, 2006), flourishing or thriving (Ryff & Singer, 1998;Seligman, 2003), benefit finding (Affleck & Tennen, 1996;Harrington, Gurk & Llewellyn, 2008), post-traumatic growth (Calhoun & Tedeschi, 2006;Hefferon, Grealy & Mutrie, 2009) or positive psychological changes (Yalom & Lieberman, 1991), among others. One of the terms that has been largely accepted is post-traumatic growth (hereinafter, PTG), since it seems to adequately capture the idea that there is a "growth", or a development beyond the level of functioning prior to the event.…”
Section: Post-traumatic Stress Disorder (Ptsd) and Posttraumatic Growmentioning
confidence: 99%
“…Despite this considerable body of research, the concept of posttraumatic growth, or the possibility that an individual can "grow" psychologically from an adverse life event, has gained increased attention in the past few years [5]. Although the term used to describe posttraumatic growth has varied across studies (e.g., "perceived benefits," "positive psychological changes," "stress-related growth") [6][7][8][9], the conceptual aim of measuring growth outcomes typically has been to assess whether individuals can in some way move beyond a premorbid level of functioning following a traumatic event [10]. Thus, within the posttraumatic growth framework, an adverse experience is viewed as a potential catalyst for positive psychological and interpersonal change.…”
mentioning
confidence: 99%